Antifungal drugs: What brings the future?. (10th July 2019) - Van Daele, Ruth; Spriet, Isabel; Wauters, Joost; Maertens, Johan; Mercier, Toine; Van Hecke, Sam; Brüggemann, Roger
Abstract: The high burden and growing prevalence of invasive fungal infections (IFIs), the toxicity and interactions associated with current antifungal drugs, as well as the increasing resistance, ask for the development of new antifungal drugs, preferably with a novel mode of action. Also, the availability of oral or once-weekly alternatives would enable ambulatory treatment resulting in an improved patient's comfort and therapy adherence. However, only one new azole and two new posaconazole-formulations were marketed over the last decade. This review focuses on the antifungal drugs in the pipeline undergoing clinical evaluation. First, the newest azole, isavuconazole, with its improved safety profile and reduction in DDIs, will be discussed. Moreover, there are two glucan synthase inhibitors (GSIs) in the antifungal pipeline: rezafungin (CD101), a long-acting echinocandin with an improved stability that enables once weekly administration, and SCY-078, an orally available GSI with efficacy against azole- and echinocandin resistant isolates. A new oral formulation of amphotericin B will also be presented. Moreover, the first representative of a new antifungal class, the orotomides, with a broad spectrum and no cross-resistance with current antifungal classes, will be discussed. Finally, an overview of other antifungals that are still in earlier clinical development phases, is provided.